A Pythagoras Tree Shape Fractal Antenna for Multiband Applications - K Tirupathi Rao, S. Leelashyam, B Narasimha Rao (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Given a large graph G = (V, E) with millions of nodes and edges, how do we compute its connected components efficiently? Recent work addresses this problem in map-reduce, where a fundamental trade-off exists between the number of map- reduce rounds and the communication of each round. Denoting d the diameter of the graph, and n the number of nodes in the largest component, all prior techniques for map-reduce either require a linear, Θ(d), number of rounds, or a quadratic, Θ(n|V | + |E|), communication per round. We propose here two efficient map-reduce algorithms: (i) Hash-Greater-to-Min, which is a randomized algorithm based on PRAM techniques, requiring O(log n) rounds and O(|V | + |E|) communication per round, and (ii) Hash-to-Min, which is a novel algorithm, provably finishing in O(log n) iterations for path graphs. The proof technique used for Hash-to-Min is novel, but not tight, and it is actually faster than Hash-Greater-to- Min in practice. We conjecture that it requires 2 log d rounds and 3(|V | + |E|) communication per round, as demonstrated in our experiments. Using secondary sorting, a standard map- reduce feature, we scale Hash-to-Min to graphs with very large connected components. Our techniques for connected components can be applied to clustering as well. We propose a novel algorithm for agglomera- tive single linkage clustering in map-reduce. This is the first map- reduce algorithm for clustering in at most O(log n) rounds, where n is the size of the largest cluster. We show the effectiveness of all our algorithms through detailed experiments on large synthetic as well as real-world datasets